2021
DOI: 10.2166/wh.2021.184
|View full text |Cite
|
Sign up to set email alerts
|

Water use behaviors and water access in intermittent and continuous water supply areas during the COVID-19 pandemic

Abstract: More than one billion people worldwide receive intermittent water supply (IWS), in which water is delivered through a pipe network for fewer than 24 h/day, limiting the quantity and accessibility of water. During the COVID-19 pandemic, stay-at-home orders and efforts to limit contact with others can affect water access for those with unreliable home water supplies. We explored whether water service delivery and household water-use behaviors changed during the COVID-19 pandemic in Hubballi–Dharwad, India, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Current recommendations for the use of plain soap are consistent with findings from a systematic review that suggest that plain soap is more effective than antibacterial soap at removing or inactivating pathogens on hands in community settings 80. Recommendations for running water are equally relevant as unreliable water supply negatively affects households’ ability to perform hand hygiene 81. Gaps in recommendations on minimum quantities of soap and water required for effective hand hygiene are also important for future guidelines to address.…”
Section: Discussionmentioning
confidence: 56%
“…Current recommendations for the use of plain soap are consistent with findings from a systematic review that suggest that plain soap is more effective than antibacterial soap at removing or inactivating pathogens on hands in community settings 80. Recommendations for running water are equally relevant as unreliable water supply negatively affects households’ ability to perform hand hygiene 81. Gaps in recommendations on minimum quantities of soap and water required for effective hand hygiene are also important for future guidelines to address.…”
Section: Discussionmentioning
confidence: 56%
“…Like what has been noted in this study, a study among health workers in Zimbabwe identified lack of running water in the community in health care settings as one of the factors fuelling transmission of COVID-19 in the country [ 18 ]. Intermittent and insufficient water for hand washing during the COVID-19 pandemic was also reported in India [ 34 ]. Thus, vulnerable communities are sometimes willing to comply with hand hygiene and other preventive measures but lack the resources to do so.…”
Section: Discussionmentioning
confidence: 99%
“…It means that in the periods of Wave 1 and Wave 2, the findings of Piped_water agree with one study in Brazil in 2020 [ 59 ]. Undeniably, insufficient or unreliable water supply can aggravate poor sanitation, discourage hygiene practices and spread diseases in densely populated areas [ 69 ]. On the other hand, the opposite effects of Pop_65 in different temporal periods might suggest that the elderly population is probably more willing to adhere to preventive measures after they become aware of the seriousness of the COVID-19 situation in Sarawak in the first half of 2021.…”
Section: Discussionmentioning
confidence: 99%